Divergences of generalized quantum electrodynamics on the Lorenz gauge - Bufalo, R. [UNESP] (2013)
In this paper we study the Generalized Quantum Electrodynamics (GQED4) on the Lorenz gauge condition and show that divergences are still present in the theory. © 2013 American Institute of Physics.